Unusual 9-->10 rearrangement of the substituted cage carbon in the ferratricarbollide series. Synthesis of the isomeric complexes [2-eta 5-(C5H5)-10-X-closo-2,1,7,10-FeC3B8H10] (where X = H2N, MeHN, Me2N, and ButHN) - Grüner, B; Lehtonen, A; Kivekäs, R; Sillanpää, R; Holub, J; Teixidor, F; Viñas, C; Stíbr, B (Inorganic chemistry, 2000)
Treatment of the zwitterionic amine tricarbollides of general formula 7-L-nido-7,8,9-C3B8H10 (1) (where L = Me2HN (1c) and ButH2N (1d)) with [(eta 5-C5H5)Fe(CO)2]2 in refluxing mesitylene resulted in the formation of a mixture of the known compounds [2-(eta 5-C5H5)-9-X-closo-2,1,7,9-FeC3B8H10] (2) (where X = H2N (2a), Me2N (2c), and ButHN (2d)) and a series of new, isomeric ferratricarbollylamines [2-(eta 5-C5H5)-10-X-closo-2,1,7,10-FeC3B8H10] (3) (where X = H2N (3a), Me2N (3c), and ButHN (3d)) in moderate yields. Complexes of type 3 (where X = H2N (3a), MeHN (3b), Me2N (3c), and ButHN (3d)) were also obtained readily by heating complexes of type 2 (where X = H2N (2a), MeHN (2b), Me2N (2c), ButHN (2d), and Bu(t)(Me)N (2e)) at ca. 300 degrees C for 10 min. All the complexes of type 3 contain reactive amine functions in meta positions with respect to the metal center. The observed 9-->10 rearrangement of the substituted cluster carbon is quite unexpected and is believed to result from higher thermodynamic stability of the 10-substituted isomers. The structures of all compounds of type 3 were established by high-field NMR spectroscopy and mass spectrometry, and that of 3d was determined by an X-ray diffraction study.